Conflict characters of daughter against Her parentsas seen in jodipicoult’s My sister’s keeper - Wastina Sarumaha (Fakultas Sastra Universitas Ekasakti, 2017)
The thesis discusses about novel my sister’s keeper written by Jodi picoult. This novel describes the relationship between a family that has a complicated problem between the child and the mother. Problems that occur in the family is caused by the favoritism of parents to their children and one of the family members suffered severe disease in this novel.